2010
DOI: 10.1007/s00269-010-0398-8
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure thermo-elastic properties of beryl (Al4Be6Si12O36) from ab initio calculations, and observations about the source of thermal expansion

Abstract: Ab initio calculations of thermo-elastic properties of beryl (Al 4 Be 6 Si 12 O 36 ) have been carried out at the hybrid HF/DFT level, by using the B3LYP and WC1LYP Hamiltonians. Static geometries and vibrational frequencies were calculated at different values of the unit cell volume, to get static pressure and mode-γ Grüneisen's parameters. Zero point and thermal pressures were calculated by following a standard statistical-thermodynamic approach, within the limit of the quasiharmonic approximation, and added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 42 publications
4
60
1
2
Order By: Relevance
“…Their resultant bulk modulus is in reasonable agreement with those in the studies of Hazen et al (1986) (170 GPa) and Prencipe and Nestola (2005) (179 GPa) under uncertainties, but is far different from the results of Qin et al (2008) (226 GPa). Additionally, Prencipe et al (2011) predicted a phase transition of zone-center soft mode from P6/mcc to P1 at a pressure about 14 GPa by theoretical calculation. However, Qin et al (2008) stated that no evidence for the phase transition of beryl was observed in the range of experimental pressure up to 19.2 GPa.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Their resultant bulk modulus is in reasonable agreement with those in the studies of Hazen et al (1986) (170 GPa) and Prencipe and Nestola (2005) (179 GPa) under uncertainties, but is far different from the results of Qin et al (2008) (226 GPa). Additionally, Prencipe et al (2011) predicted a phase transition of zone-center soft mode from P6/mcc to P1 at a pressure about 14 GPa by theoretical calculation. However, Qin et al (2008) stated that no evidence for the phase transition of beryl was observed in the range of experimental pressure up to 19.2 GPa.…”
Section: Introductionmentioning
confidence: 96%
“…However, there are few reports in the literature about the elasticity of beryl at high pressure (Yoon and Newnham 1973;Hazen et al 1986;Prencipe and Nestola 2005;Qin et al 2008), especially for the thermoelasticity of beryl at simultaneously high pressure and high temperature (Prencipe et al 2011). Hazen et al (1986) investigated the compressibility and high-pressure behavior of beryl at high pressure up to 6 GPa using a diamond anvil cell and obtained the value of 170 (5) GPa for bulk modulus K 0 under the assumption of its pressure derivative (K ′ 0 ) to be 4.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The Vibrational Density Of State (VDOS) diagrams for DOL1 are shown in Figure 2, 176 following the procedure described in Prencipe et al (2011). In Table 1 and Mg polyhedra behave differently with P ( Figure S1 in the "Supplementary Material" section ).…”
Section: Starting Configurations 134 135mentioning
confidence: 99%